Abdominal Surgical Procedures in Adult Patients With Cystic Fibrosis: What Are the Risks?. Issue 8 (5th July 2022) - Hite, Melissa A.; Gaertner, Wolfgang B.; Garcia, Bryan; Flume, Patrick A.; Maxwell, Pinckney J.; George, Virgilio V.; Curran, Thomas
Abstract : BACKGROUND: With advances in medical care, patients with cystic fibrosis are more commonly living into adulthood, yet there are limited data describing the need for GI surgery and its outcomes in adult cystic fibrosis patients. OBJECTIVE: We aim to use a national administrative database to evaluate trends in abdominal GI surgery and associated postoperative outcomes among adult cystic fibrosis patients. DESIGN: This was a national retrospective cohort study. SETTING: A national all-payor administrative database from 2000 to 2014 was used. PATIENTS: Patients included adults (age ≥18 years) with cystic fibrosis undergoing abdominal GI surgery. MAIN OUTCOME MEASURES: The primary outcome was trend over time in number of surgical admissions. Secondary outcomes included morbidity and mortality by procedure type. RESULTS: We identified 3075 admissions for abdominal surgery, of which 28% were elective. Major GI surgical procedures increased over the study period ( p < 0.01), whereas appendectomy and cholecystectomy did not demonstrate a clear trend ( p = 0.90). The most common procedure performed was cholecystectomy ( n = 1280; 42%). The most common major surgery was segmental colectomy ( n = 535; 18%). Obstruction was the most common surgical indication ( n = 780; 26%). For major surgery, in-hospital mortality was 6%, morbidity was 37%, and mean length of stay was 15.9 days (SE 1.2). LIMITATIONS: The study is limited by a lack of granular physiological and clinical data within the administrative data source. CONCLUSIONS: Major surgical admissions for adult patients with cystic fibrosis are increasing, with the majority being nonelective. Major surgery is associated with significant morbidity, mortality, and prolonged length of hospital stay. These findings may inform perioperative risk for adult patients with cystic fibrosis in need of GI surgery. See Video Abstract at http://links.lww.com/DCR/B850 . PROCEDIMIENTOS QUIRÚRGICOS ABDOMINALES EN PACIENTES ADULTOS CON FIBROSIS QUÍSTICA: ¿CUÁLES SON LOS RIESGOS?: ANTECEDENTES: Con los avances en la medicina, los pacientes con fibrosis quística viven más comúnmente hasta la edad adulta, pero hay datos escasos que describan la necesidad de cirugía gastrointestinal y sus resultados en pacientes adultos con fibrosis quística. OBJETIVO: Nuestro objetivo es utilizar una base de datos administrativa nacional para evaluar las tendencias en la cirugía gastrointestinal abdominal y los resultados posoperatorios asociados entre los pacientes adultos con fibrosis quística. DISEÑO: Estudio de cohorte retrospectivo nacional. AJUSTE: Base de datos administrativa nacional de todas las instituciones pagadoras desde 2000 a 2014. PACIENTES: Todos los pacientes adultos (edad> 18) con fibrosis quística sometidos a cirugía gastrointestinal abdominal. PRINCIPALES MEDIDAS DE RESULTADO: El resultado primario fue la tendencia a lo largo del tiempo en el número de ingresos quirúrgicos. Los resultados secundarios incluyeron morbilidad y mortalidad por tipo de procedimiento. RESULTADOS: Identificamos 3.075 ingresos por cirugía abdominal de los cuales el 28% fueron electivos. Los procedimientos quirúrgicos gastrointestinales mayores aumentaron durante el período de estudio (p <0, 01) mientras que la apendicectomía y la colecistectomía no demostraron una tendencia clara (p = 0, 90). El procedimiento realizado con mayor frecuencia fue la colecistectomía (n = 1.280; 42%). La cirugía mayor más común fue la colectomía segmentaria (n = 535; 18%). La obstrucción fue la indicación quirúrgica más común (n = 780; 26%). Para la cirugía mayor, la mortalidad hospitalaria fue del 6%, la morbilidad del 37% y la estadía media de 15, 9 días (EE 1, 2). LIMITACIONES: El estudio está limitado por la falta de datos clínicos y fisiológicos granulares dentro de la fuente de datos administrativos. CONCLUSIONES: Los ingresos quirúrgicos mayores de pacientes adultos con fibrosis quística están aumentando y la mayoría no son electivos. La cirugía mayor se asocia con una morbilidad y mortalidad significativas y una estancia hospitalaria prolongada. Estos hallazgos pueden informar el riesgo perioperatorio para pacientes adultos con fibrosis quística que necesitan cirugía gastrointestinal. Consulte Video Resumen en http://links.lww.com/DCR/B850 . (Traducción—Dr. Felipe Bellolio )